Pro SharePoint 2010 administration - Garrett, Robert (Apress, 2011)
Pro SharePoint 2010 administration is a practical guide to SharePoint 2010 for intermediate to advanced SharePoint administrators and power users, covering the out-of-the-box feature set and capabilities of Microsoft's collaboration and business productivity platform. SharePoint 2010 is an incredibly complex product, with many moving parts, new features, best practices, and "gotchas." Author Rob Garrett distills SharePoint's portfolio of features, capabilities, and utilities into an in-depth professional guide"with no fluff and copious advice"that is designed from scratch to be the manual Microsoft never wrote. Starting with a detailed deployment and initial configuration walkthrough, the book covers all major feature areas, including document management, social computing, metadata management, and administration. You'll also learn about planning for capacity, backup administration and disaster recovery, business intelligence, monitoring, and more. Unlike other books, Pro SharePoint 2010 Administration covers all elements of the product, but has a specific emphasis on features new and enhanced in the 2010 release. Pro SharePoint 2010 Administration is the only book you'll need as you set out to deploy and administer SharePoint 2010.